Project Report on Security System using Vx Works - ANISH MATHEW, JOBBY JOHN, MANOJ KUMAR D and SAMUEL JOSEPH (2002)
INTERNAL GUIDE: A A SHOLAPUR, MVJCE EXTERNAL GUIDE: SHNOJ K BABY, IBS
Keywords: Security System using Vx Works